Subjects suffering in resistance: an approach to the subjectivities of the Colombian armed conflict. - Beatriz Elena Arias López (Social Medicine Publication Group, 2018)
In this paper we report on the results of an investigation carried out with peasant communities in the Department of Antioquia, Colombia. This research grew from a critique of the biomedical model's shortcomings in accounting for the relationship between political violence and mental health in the medium and long term. This dynamic is especially relevant in the Colombian context where, after decades of armed conflict, a transformation has begun following the signing of a peace treaty and negotiations with the country's two last remaining guerrilla groups. Questions about the relationship between mental health and armed conflicts are not new; they appeared after the First World War, gaining full legitimacy after the establishment of the World Health Organization (WHO) in the aftermath of the Second World War. Within this literature, there has been a tendency to give greater relevance to clinical and epidemiological studies that explore short-term effects, with an emphasis on Posttraumatic Stress Disorder (PTSD) and other psychiatric diagnoses. Unfortunately, such research has neglected pressing questions, concerning the subjectivities that take shape in the medium and long term horizons of prolonged armed conflicts.